1998
DOI: 10.1101/gad.12.12.1787
|View full text |Cite
|
Sign up to set email alerts
|

A novel protein complex that interacts with the vitamin D3 receptor in a ligand-dependent manner and enhances VDR transactivation in a cell-free system

Abstract: Steroid, retinoid, vitamin D 3 , and thyroid hormones signal through ligand-dependent transcription factors that collectively comprise a superfamily of intracellular, soluble receptors (hereafter collectively called nuclear receptors) that reside in the nucleus or translocate there in response to hormonal signals. As the largest known family of eukaryotic transcriptional regulators, nuclear receptors are implicated via the target genes they modulate in the control of cell growth and differentiation, homeostasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
246
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 357 publications
(253 citation statements)
references
References 63 publications
6
246
1
Order By: Relevance
“…The multisubunit DRIP (VDR-Interacting Protein) complex also binds to VDR in response to the ligand vitamin D [8,9]. This interaction occurs through the LBD of VDR in the same manner as the p160/SRC coactivators, resulting in transcriptional enhancement [10].…”
Section: Components Of Regulatory Complexesmentioning
confidence: 99%
“…The multisubunit DRIP (VDR-Interacting Protein) complex also binds to VDR in response to the ligand vitamin D [8,9]. This interaction occurs through the LBD of VDR in the same manner as the p160/SRC coactivators, resulting in transcriptional enhancement [10].…”
Section: Components Of Regulatory Complexesmentioning
confidence: 99%
“…Binding of cellular proteins to immobilized GST fusion proteins was carried out essentially according to Rachez et al (1998). Two cDNA fragments encompassing MN1 amino acids 48-256 and 365-520 were fused in frame with the pGEX3X vector (Pharmacia).…”
Section: Gst Fusion Protein Pull-downsmentioning
confidence: 99%
“…While the order of events occurring during this process and the mechanism by which it occurs are less well de®ned, several studies have provided information which allow us to speculate as to what may be occurring. Indeed, roles for the SWI/ SNF and SMCC (Fondell et al, 1996;Rachez et al, 1998Rachez et al, , 1999 complexes have been shown during this stage of the initiation process in vitro. Based on these studies, we suggest that the fourth step could be an exchange of coactivators at the AF-2 surface of the NR-LBD.…”
Section: Introductionmentioning
confidence: 99%